Severity of Nonalcoholic Fatty Liver Disease is Associated With Cardiovascular Outcomes in Patients With Prehypertension or Hypertension: A Community–Based Cohort Study - Song, Qi–Rui; Liu, Shuo–Lin; Ling, Qian-Hui; Gao, Qian-Nan; Yang, Rui-Xue; Chen, Shuo-Hua; Wu, Shou–Ling; Chen, Mu-Lei; Cai, Jun (Frontiers in Endocrinology, 2022)
Background: It is unclear whether more severe non–alcoholic fatty liver disease (NAFLD) combined with prehypertension or hypertension is associated with a higher risk of cardiovascular events (CVEs). To evaluate the relationship between the severity of NAFLD and CVEs among patients with prehypertension or hypertension. Methods: In this prospective community–based Kailuan cohort, participants without cardiovascular disease and alcohol abuse, or other liver diseases were enrolled. NAFLD was diagnosed by abdominal ultrasonography. Prehypertension was defined as systolic blood pressure (BP) of 120–139 mmHg or diastolic BP of 80–89 mmHg. Participants with NAFLD were divided into mild, moderate, and severe subgroups. Follow–up for CVEs including myocardial infarction, hemorrhagic stroke, and ischemic stroke. The Cox proportional hazards model was used to estimate hazard ratios and 95% CIs of CVEs according to the severity of NAFLD and hypertensive statutes. The C-statistic was used to evaluate the efficiency of models. Results: A total of 71926 participants (mean [SD] age, 51.83 [12.72] years, 53794 [74.79%] men, and 18132 [25.21%] women) were enrolled in this study, 6,045 CVEs occurred during a median of 13.02 (0.65) years of follow–up. Compared with participants without NAFLD, the hazard ratios of CVEs for patients with mild, moderate, and severe NAFLD were 1.143 (95% CI 1.071–1.221, P < 0.001), 1.218 (95% CI 1.071–1.221, P < 0.001), and 1.367 (95% CI 1.172–1.595, P < 0.001), respectively. Moreover, participants with prehypertension plus moderate/severe NAFLD and those with hypertension plus moderate/severe NAFLD had 1.558–fold (95% CI 1.293–1.877, P < 0.001) and 2.357–fold (95% CI 2.063–2.691, P < 0.001) higher risks of CVEs, respectively, compared with those with normal BP and no NAFLD. Adding a combination of NAFLD and BP status to the crude Cox model increased the C–statistic by 0.0130 (0.0115–0.0158, P < 0.001). Conclusions: Our findings indicated that the increased cardiovascular risk with elevated BP is largely driven by the coexistence of moderate/severe NAFLD, suggesting that the severity of NAFLD may help further stratify patients with prehypertension and hypertension.